"TRAP is legit!" using self-regulated strategy development to teach reading comprehension in a residential treatment facility. Issue 1 (2nd January 2022) - Sanders, Sara; Hart Rollins, Lauren; Michael, Elizabeth; Jolivette, Kristine
ABSTRACT: This study investigated the effectiveness of the self-regulated strategy development (SRSD) instructional approach with middle school youth with behavior challenges served in a residential treatment facility. Youth were taught the TRAP (T hink before reading, R ead a paragraph, A sk what is the main idea/important details, P araphrase the paragraph; Mason et al.) mnemonic as a means of increasing reading comprehension as measured through oral retell. Using a multiple-probe across participant single case design, a functional relation between the TRAP mnemonic and oral retell scores was observed. Treatment fidelity, social validity, and academic engagement are presented. Implications for practitioners, limitations, and areas for future directions are outlined.